Phytochemicals From Garcinia, Mesua and Jatropha Species and Their Biological Activities - Lim, Chan Kiang (2005)
Extensive studies on 5 plants, Garcinia penangi&, Garcinia nitih, Mesua daphnifolia, Mesua beccariana and Jatropha podagrica have resulted in the isolation of twenty one compounds. Out of these compounds two are new. All these compounds were isolated by means of chromatographic method and their structures derived on the basis of spectroscopic evidence, mainly 1D and 2D NMR SPectrO~PYChemical investigations on the stem bark extracts of Garcinia penangiana yielded a flavonoid, catechin (86) and a steroidal triterpene, stigmasterol (85) whereas the stem bark extracts of Garcinia nitida yielded two triterpenoids, stigmasterol (85) and stigmasterol acetate (87) plus a total of five xanthones, inophyllin B (88), osajaxanthone (89), 1,3,7-trihydroxy-2,4-bis(3-methylbut-2-enyl)xanthone (90), rubraxanthone (91) and 3-isomangostin (92). Meanwhile, studies on the stem bark extracts of Mesua daphnifolia yielded three triterpenoids, fiedelin (93), ftiedelan 1,3-dione (94) and lup-20(29)-en-3P-o1(96), three known xanthones, ananixanthone (95), cudraxanthone G (97) and euxanthone (52) and a new xanthone, daphnifolin (98). On the other hand, the stem bark extracts of Mesua beccariana gave two triterpenoids, stigmasterol (85) and fiiedelin (93) and a phenylcoumarin, isocalanone (99). Jatrophu podagrica afforded two triterpenoids, &sitosterol (61) and acetylaleuritolic acid (77), a cournarin, fiaxidin (101), a new ferulic acid ester, nheptyl f d a t e (100) and sucrose (102). Acetylation on rubraxanthone (91) gave two new compounds which were never reported before. These are rubraxanthone monoacetate (103) and rubraxanthone diacetate (104). The known rubraxanthone triacetate (105) was also synthesized. Cytotoxic assay was performed using CEM-SS (T-lymphoblastic leukemia) cell line. All the crude extracts of Garcinia penangiana and Jaheophu jwdagrica, the crude hexane extract of Mesua beccariana and the crude hexane and chloroform extracts of Garcinia nitida were found to show significant growth inhibitory activities with ICso values of less than 30 pg/ml. Cytotoxic assays were also carried out on the pure compounds towards the CEM-SS (T-lymphoblastic leukemia), HeLa (cervical carcinoma), MDA-MB-231 (human estrogen receptor negative breast cancer) and CaOV3 (human ovarian cancer) cell lines. Cudraxanthone G (97) and fiiedelan-13-&one (94) were found to show strong inhibitory activities toward the HeLa cell line with ICso values of 4.0 and 4.6 pg/ml respectively. Both cudraxanthone G (97) and rubraxanthone (91) gave moderate inhibitory activities with ICso values of 6.7 and 9.4 pg/ml respectively towards the CEM-SS cell line. The MDA-MB-231 cell line was found to be very susceptible towards most of the prenylated xanthones tested: cudraxanthone G (97) (ICSo = 1.3 pghl), inophyllin B (88) (ICso = 1.4 pg/ml), 1,3,7-trihydroxy-2,4-bis(3-methylbut- 2enyl)xanthone (90) (IC9 = 2.2 pg/ml) and ananixantone (95) (ICso = 4.6 pg/ml). Meanwhile, emanthone (52) gave a moderate activity (ICso = 9.0 pg/ml) towards the CaOV3 cell line. Most of the compounds tested indicated selective activity towards the cancer cell lines except for cudraxanthone G (97) which was found to have a broad spectrum of activities. Antimicrobial assays were carried out towards four pathogenic bacteria: Methicillin Resistant Staphylococcus awes, Pseudomonas aeruginosa, Salmonella typhimurium and Bacillus subtilis. Most of the crude extracts tested against these microbes gave only moderate or weak activities except for the ethyl acetate extract of Jah-opha podagrica, which was strongly active against the microbe Pseudomonas aeruginosa with an inhihition width of 15 ram which is close to that of the standard, streptomycin sulphate (1 6 mm). Larvicidal tests were carried out against the larvae of Aedes aegvpti. The larvae were strongly susceptible to the hexane and chloroform extracts of Mesua daphnifolia with LCso values of as low as 9.7 and 6.0 pprn respectively while the other crude extracts gave LC5() values of more than 60 ppm. The pure compound, rubraxanthone (91) indicated a strong larvicidal activity with LCso value of 15.5 ppm Antifungal assays were also carried out on the crude extracts of Mesua &phn#iolia towards the microbes, Candida albican, Aspergillus ochraceaus, Sacchoromyces cerevisiae and Candida lypolytica. All the crude extracts of Mesua daphnifolia exhibited moderate activities towards the microbe Candida lpolyta but they were not active against the other targeted microbes.